SISTEM INFORMASI ARSIP DIGITAL KAMPUNG MATARA: SOLUSI INOVATIF BERBASIS EXCEL MACRO UNTUK EFISIENSI PELAYANAN ADMINISTRATIF - Frederikus, Frederikus Antonius; Nurkholis Syukron; Syahrabudin Husein Enala (Nusantara Hasana Journal, 2025)
Effective and well-organized village administrative services are essential for supporting good governance. However, many villages in Indonesia still rely on manual and unstructured archiving systems that are inefficient and prone to document loss. This condition was also found in Matara Village, Merauke Regency. This community service program aims to improve the efficiency of administrative services through the implementation of a digital archiving information system based on Microsoft Excel Macro as an appropriate technology solution. The method employed a participatory qualitative approach involving observation, interviews, system development, training, mentoring, and evaluation. The results indicate that the digital archiving system significantly accelerates document retrieval, improves administrative orderliness, and enhances the capacity of village officials to utilize simple information technology. The system operates offline, is easy to use, and is well suited to the village’s limited infrastructure conditions. This program demonstrates that context-based and simple technological innovations can generate tangible and sustainable impacts on improving administrative service quality and strengthening village governance.